2018
DOI: 10.1016/j.rmcr.2018.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic empyema and pectoral abscess resulting from attempting suicide by injection of benzene in the pleural cavity

Abstract: BackgroundExposure to hydrocarbon compounds, such as benzene may cause injury to several organ systems. It occurs accidentally or intentionally by ingestion, inhalation, cutaneous exposure and either subcutaneous injection or intravenous injection. We report a patient who injected benzene into the left hemithorax and secondly attempted to commit suicide with paracetamol.Case presentationA 52-year old man was admitted in the hospital because of an attempted suicide with an injection of benzene in the left hemit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Studies have shown that the expression of m-RNA in the blood of workers exposed to benzene for a long time is different from that of normal people [3]. Some people even take advantage of the toxicity of benzene to body to commit suicide [4]. Occupational benzene poisoning is a common occupational disease in the industrial factories of big cities [5], which can be classified as acute occupational benzene poisoning and chronic occupational benzene poisoning [6].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the expression of m-RNA in the blood of workers exposed to benzene for a long time is different from that of normal people [3]. Some people even take advantage of the toxicity of benzene to body to commit suicide [4]. Occupational benzene poisoning is a common occupational disease in the industrial factories of big cities [5], which can be classified as acute occupational benzene poisoning and chronic occupational benzene poisoning [6].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the expression of m-RNA in the blood of workers exposed to benzene for a long time is different from that of normal people [3] . Some people even take advantage of the toxicity of benzene to body to commit suicide [4] . Occupational benzene poisoning is a common occupational disease in the industrial factories of big cities [5] , which can be classi ed as acute occupational benzene poisoning and chronic occupational benzene poisoning [6] .…”
Section: Introductionmentioning
confidence: 99%